Design of Cloud Computer to Support Independent Information System Servers Universitas Islam Kuantan Singingi - Muhammad Hasyim Siregar; Nofri Wandi Al-Hafiz (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
In today's all-digital era, easy access to information systems is needed. Moreover, with the new regulation from the Minister of Education that LKD/BKD must be filled in using the SISTER application from the Ministry of Education and Culture. Previously, sister was used for lecturers who wanted to certify lecturers, so to use the server at the Kuantan Singingi Islamic University, it was enough to use a laptop with all the shortcomings. With a wider demand it is necessary to make independent cloud computing-based servers, to rent cloud computing services according to standards from sisters is very unaffordable for the UNIKS campus so that this solution will make one server machine, several Virtual Machines (VM) will be created in the CPU Server.